Peningkatan Promosi Produk Melalui Sarana Fotografi Produk dan Editing Foto - Ustyannie, Windyaning; Asih, Endang Widuri; Mawadati, Argaditia; Sulistyaningsih, Eka; Wibowo, Agus Hindarto; Sekarjati, Kartinasari Ayuhikmatin; Setyowati, Dwi; Zaitunnah, Anis (DHARMA BAKTI, 2022)
OK OC ADMA Yogyakarta is a social movement for job creation. The entrepreneurship andpeople's economy movement initiated by OK OC ADMA aims to be able to createindependence and a lot of jobs for the people of Indonesia. In addition, OK OC ADMAYogyakarta provides business stalls for entrepreneurs based on IT and provides businesscoaching and training as well as entrepreneurship guidance. However, the members of OKOC ADMA Yogyakarta still have limited knowledge in product photos and the applicationof technology, especially the creation of social media content to make it easier for membersto promote their business products. So, in this community service activity, counseling isgiven to members about the science of product photography and the photo editing processusing a smartphone so that it becomes content that can be a promotional media. The methodused for the first time was counseling OK OC ADMA members about the importance ofproduct photos and digital promotions to increase sales. After knowing the theory, thetraining participants applied product photo techniques using cellphones and registered forsocial media, such as Facebook Business and Instagram. Then the participants download aphoto editing application and start creating content using the product photos they alreadyhave. From the results of the counseling carried out by the service, product photos and thecreation of promotional content can be done independently in the future. Product photos andphoto editing so that they become promotional content can ease the burden on entrepreneursin promoting all over through online media, which can indirectly help increase the reach oftheir product promotions.